Persistent ovarian masses and pregnancy outcomes. (July 2013) - Goh, William A.; Rincon, Monica; Bohrer, Justin; Tolosa, Jorge E.; Sohaey, Roya; Riaño, Rene; Davis, James; Zalud, Ivica
Abstract Objective: To determine if persistent ovarian masses in pregnancy are associated with increased adverse outcomes. Methods: This is a retrospective cohort of 126 pregnant women with a persistent ovarian mass measuring 5 cm or greater who delivered at two university hospitals between 2001 and 2009. Maternal outcomes included gestational age (GA) at diagnosis, delivery and surgery as well as miscarriage, preterm birth (PTB), ovarian torsion and hospital admission for pain. Neonatal outcomes included birth weight, respiratory distress syndrome (RDS), intra-ventricular hemorrhage (IVH), death and sepsis. Results: A total of 1225 ovarian masses were identified (4.9%) in 24 868 patients. A persistent ovarian mass was found in 0.7%. Average GA at diagnosis was 17.8 weeks. Miscarriage rate was 3.3%. Average GA at delivery was 37.9 weeks. Of the patients, 8.5% had ovarian torsion, 10.3% had admission for pain and 9.3% had PTBs. The mean cesarean delivery rate was 46.3%. The average neonatal weight was 3273 g. There was one neonatal death in this cohort. The rate of RDS was 2.8%, IVH 0.9% and neonatal sepsis 1.9%. The most common surgical pathologic diagnosis was dermoids (37.6%). No overt malignancies were seen. Conclusion: A persistent ovarian mass in pregnancy does not confer an increased risk of adverse pregnancy outcomes.